Meta-Analysis the Efficacy of Turmeric (Curcuma domestica) in Reducing Pain in Patients of Knee Osteoarthritis - Ardiyanto, Danang; Tamtomo, Didik Gunawan; Murti, Bhisma (Indonesian Journal of Medicine, 2021)
Background: Osteoarthritis (OA) of the knee joint has the highest prevalence among all types of rheumatic diseases. The most common symptom of knee OA is pain around the joint. Patients with OA require long treatment, especially using analgesic and anti-inflammatory drugs. Turmeric is efficacious as a pain reliever and anti-inflammatory. This study aims to estimate the magnitude of the effect of turmeric extract (Curcuma domestica) on pain in patients with knee OA compared to placebo and non-steroidal anti-inflammatory drugs (NSAIDs), based on the results of a number of previous similar studies.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: patients with knee OA. Intervention: turmeric extract. Comparison: placebo and NSAIDs. Outcome: pain reduction. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles: “Knee Osteoarthritis” OR “Knee OA” AND “Curcuma longa” OR “Curcuma domestica” OR “Turmeric extract” AND “Placebo” OR “NSAID” AND “pain” OR “visual analogue scale” OR “ VASE". The articles included are full-text with RCT study designs from 2011 to 2021. The selection of articles is carried out using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 15 RCT studies were selected for systematic review and meta-analysis. Data collected from 10 studies showed that patients with knee OA who received turmeric extract experienced 1.60 units lower joint pain than placebo (SMD= -1.60; 95% CI= -2.23 to -0.97; p<0.001). Data from 5 studies showed that patients with knee OA who received turmeric extract experienced 0.06 units higher joint pain than NSAIDs. The comparison between the turmeric extract group and the NSAID group did not show any significant difference (SMD= 0.06; 95% CI= -0.10 to -0.22; p= 0.490).Conclusion: Administration of turmeric extract was more effective than placebo and not inferior to non-steroidal anti-inflammatory drugs in reducing pain in patients with knee OA.Keywords: osteoarthritis, turmeric, painCorrespondence: Danang Ardiyanto. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: drdanank@gmail.com. Mobile: 08122762579.Indonesian Journal of Medicine (2021), 06(04): 364-376https://doi.org/10.26911/theijmed.2021.06.04.02